Analisa Hubungan Kecerdasan Emosi dan Penyesuaian Diri Taruna Akademi Angkatan Udara Dalam Menghadapi Era Society 5.0 - Muhammad Hero Javaniz Adjisakti; Gagat Riano; Aan Dedy Christiawan; Ismoyo Ismoyo; Limawati Handayani (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
In the era of Society 5.0, humans are faced with various challenges and social problemsthat take advantage of various technological innovations which were born in the era of the industrial revolution 4.0. As a solution to these problems, education has an important role to improve the quality of Human Resources (HR). For this reason, the Air Force Academy (AAU) as one of the official educational institutions that prepares human resources in the military world, has an important mission to improve the quality of its education in order to prepare the cadets to face the era of Society 5.0. As the first step of education at AAU which will be taken for four years, cadets are required to be able to adapt to the military environment, which is clearly much different from their previous world. One important factor in self-adjustment is emotional intelligence. Thus, it is necessary to conduct research on the influence of emotional intelligence on the adjustment of cadets in attending education at the AAU as part of the readiness of the AAU's role to prepare Indonesian Air Force human resources in the era of society 5.0. In this study, the method used is the correlative quantitative method to see the relationship between one or several variables with other variables. Based on the research, it was found that emotional intelligence was strongly correlated with the adjustment of AAU cadets (R=0.647 and R2= 0.418). ME for both variables is included in the high level of category, with the ME value of emotional intelligence at 103.6974 and self-adjustment at 24.651. Thus, seriousness in the implementation of education and training needs more attention as capital in forming Indonesian Air Force officers who are ready to face Society 5.0.